Comparison of biological measurement and physical estimates of space radiation in the International Space Station. Issue 8 (August 2022) - Yoshida, Kayo; Hada, Megumi; Kizu, Akane; Kitada, Kohei; Eguchi-Kasai, Kiyomi; Kokubo, Toshiaki; Teramura, Takeshi; Yano, Sachiko; Suzuki, Hiromi Hashizume; Watanabe, Hitomi; Kondoh, Gen; Nagamatsu, Aiko; et al.
Abstract: Nowadays, ordinary people can travel in space, and the possibility of extended durations in an environment such as moon of the Earth and Mars with higher space radiation exposures compared to past missions, is increasing. Until now, the physical doses of space radiation have been measured, but measurement of direct biological effects has been hampered by its low dose and low dose-rate effect. To assess the biological effects of space radiation, we launched and kept frozen mouse embryonic stem (ES) cells in minus eighty degree Celsius freezer in ISS (MELFI) on the International Space Station (ISS) for a maximum of 1, 584 days. The passive dosimeter for life science experiments in space (PADLES) was attached on the surface of the sample case of the ES cells. The physical dosimeter measured the absorbed dose in water. After return, the frozen cells were thawed and cultured and their chromosome aberrations were analyzed. Comparative experiments with proton and iron ion irradiation were performed at particle accelerators on Earth. The wild-type ES cells showed no differences in chromosomal aberrations between the ground control and ISS exposures. However, we detected an increase of chromosome aberrations in radio-sensitized histone H2AX heterozygous-deficient mouse ES cells and found that the rate of increase against the absorbed dose was 1.54-fold of proton irradiation at an accelerator. On the other hand, we estimated the quality factor of space radiation as 1.48 ± 0.2. using formulas of International Commission of Radiation Protection (ICRP) 60. The relative biological effectiveness (RBE) observed from our experiments (1.54-fold of proton) was almost equal (1.04-fold) to the physical estimation (1.48 ± 0.2). It should be important to clarify the relation between biological effect and physical estimates of space radiation. This comparative study paves a way to reveal the complex radiation environments to reduce the uncertainty for risk assessment of human stay in space. Abstract : International space station, Space radiation, Mouse ES Cells, Stem cells, Chromosome aberration, Risk assessment.